2011
DOI: 10.1097/jto.0b013e318226b4a6
|View full text |Cite
|
Sign up to set email alerts
|

BV6, an IAP Antagonist, Activates Apoptosis and Enhances Radiosensitization of Non-small Cell Lung Carcinoma In Vitro

Abstract: Introduction Defects in the apoptosis pathway limit the effectiveness of radiation in non-small cell lung cancer (NSCLC) therapy. BV6 is an antagonist of cIAP1 and XIAP, members of the inhibitors of apoptosis (IAP) family. We investigated the potential of BV6 to sensitize NSCLC cell lines to radiation. Methods HCC193 and H460 lung cancer cell lines were treated with BV6 to investigate the effects of drug administration on cell proliferation, apoptosis, inhibition of XIAP and cIAP1, and radiosensitivity. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…31,48,49 Our findings showing that BV6 cooperates together with Obatoclax to induce cell death in CLL cells, but not together with ABT-263 may be related to the differential activity profiles of these BH3 mimetics, as Obatoclax antagonizes BCL-2, BCL-xL, BCL-W and MCL-1, whereas ABT-263 targets BCL-2, BCL-xL and BCL-W, but not MCL-1. 50 Single-agent cytotoxicity of Smac mimetic compounds has been reported for CLL, 40 multiple myeloma or 2, 12, 17, 39) were treated for indicated times with 10 mM BV6, 1 mM Staurosporine and 20 mM zVAD.fmk alone or in combination.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…31,48,49 Our findings showing that BV6 cooperates together with Obatoclax to induce cell death in CLL cells, but not together with ABT-263 may be related to the differential activity profiles of these BH3 mimetics, as Obatoclax antagonizes BCL-2, BCL-xL, BCL-W and MCL-1, whereas ABT-263 targets BCL-2, BCL-xL and BCL-W, but not MCL-1. 50 Single-agent cytotoxicity of Smac mimetic compounds has been reported for CLL, 40 multiple myeloma or 2, 12, 17, 39) were treated for indicated times with 10 mM BV6, 1 mM Staurosporine and 20 mM zVAD.fmk alone or in combination.…”
Section: Discussionmentioning
confidence: 82%
“…Mean and SEM of 17 individual CLL samples measured in duplicate or triplicate (samples no. 2,6,8,12,15,17,18,19,24,28,33,36,39,41,43,48,50) 2,6,8,12,15,17,18,19,24,28,33,36,39,41,43,48,50) are shown; *p < 0.05. several solid tumors, 16,35,36,[51][52][53] while another study showed that CLL cells remain resistant against Smac mimetics in the context of CD40 ligand stimulation. 39 Compared with CLL cells, BV6 showed little cytotoxicity against non-malignant B-cells, a finding also reported by other investigators in CLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 One of the recently developed SMAC mimetics is BV6, which binds to BIR domains of IAPs leading to their ubiquitination, followed by proteosomal degradation and inhibition of XIAP-mediated inhibition of caspases. 25,26 In the present study, we sought to explore the cytotoxic effects of BV6 in numerous human cancer cells. Besides, we studied the sensitizing potential of BV6 on TNF-a and TRAILinduced apoptosis as a novel strategy for combinational antitumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The cIAP1 expression, rather than XIAP expression, evidently increased in Hela cells after AT-406 treatment. Other studies also found that IAP antagonists induced rapid cIAP1 degradation, which is a key early event in IAP antagonist-induced apoptosis in sensitive cancer cells (28,29). This phenomenon may be associated with the function of the RING-finger of cIAP1 as an active E3 center.…”
Section: Discussionmentioning
confidence: 96%